2019
DOI: 10.1186/s40035-019-0147-y
|View full text |Cite
|
Sign up to set email alerts
|

Blocking meningeal lymphatic drainage aggravates Parkinson’s disease-like pathology in mice overexpressing mutated α-synuclein

Abstract: Background Abnormal aggregation of brain α-synuclein is a central step in the pathogenesis of Parkinson’s disease (PD), thus, it is reliable to promote the clearance of α-synuclein to prevent and treat PD. Recent studies have revealed an essential role of glymphatic system and meningeal lymphatic vessels in the clearance of brain macromolecules, however, their pathophysiological aspects remain elusive. Method Meningeal lymphatic drainage of 18-week-old A53T mice was blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
191
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(228 citation statements)
references
References 70 publications
4
191
0
1
Order By: Relevance
“…Therefore, brain lymphatic vessels play an important role in collecting brain metabolites, draining waste products into nearby lymph nodes and helping the brain maintain homeostasis. Moreover, it has been demonstrated that brain lymphatic clearance dysfunction could participate in the pathogenesis of neurodegenerative diseases . In line with this, we demonstrated that the BLF metabolomes from a PD model group and a control group were indeed different.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, brain lymphatic vessels play an important role in collecting brain metabolites, draining waste products into nearby lymph nodes and helping the brain maintain homeostasis. Moreover, it has been demonstrated that brain lymphatic clearance dysfunction could participate in the pathogenesis of neurodegenerative diseases . In line with this, we demonstrated that the BLF metabolomes from a PD model group and a control group were indeed different.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have proven that deep cervical lymph nodes (dCLNs) represent an important site for the drainage of mLVs from intracranial structures to the extracranial lymphatic system [5,23,24]. Different substances, such as macromolecules, fluoresceins and Evans Blue (EB), can be detected in dCLNs when they are drained through mLVs [24,43] . Furthermore, the drainage function of mLVs is significantly decreased after ligating deep cervical lymph vessels (dCLVs) [5,43], suggesting that the presence of the pathway can be indirectly demonstrated by the detection of substances in dCLNs that are injected into the subdural space.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, studies using in vivo magnetic resonance imaging (MRI) techniques have also identified the existence of meningeal lymphatic vessels in both humans and nonhuman primates [24,25]. More recent studies have also shown that the meningeal lymphatic system is critical for clearing amyloid beta, extracellular tau, and alpha synuclein from the brain, and that disruption of this drainage system can promote the accumulation of these neurotoxic DAMPs in the brain [21,26,27]. Whether meningeal lymphatic dysfunction plays a role in TBI currently remains poorly understood.…”
mentioning
confidence: 99%